Sustainable Development of Indonesia’s Native Chicken Sector: Opportunities and Constraints - Elly Tugiyanti; Wida Nurnaningsih; Tri Sukmaningsih (Journal of Sustainable Livestock, 2025)
This study provides a comprehensive descriptive analysis of the opportunities and constraints in Indonesia’s native chicken sector using a mixed-methods approach. The sector is vital, with native chickens representing 65% of local poultry populations, supporting rural livelihoods and food security. Quantitative findings reveal an average flock size of 150 birds, annual production of 120 eggs per hen, and a 15% mortality rate. Market analysis shows 70% of farmers participate locally, with chicken activities contributing 25% to household income. Cluster analysis identified three main production typologies: traditional scavenging, semi-intensive, and integrated backyard systems. Key constraints include disease susceptibility (notably Newcastle Disease), feed limitations, and low hatchability (78%). While sustainability indices show strong social and environmental scores, economic viability remains low due to high costs and limited credit. A SWOT analysis highlights opportunities, such as rising consumer demand for native breeds, but also weaknesses like poor infrastructure and inadequate technical support. The study found a positive correlation (r=0.65) between biosecurity practices and hatchability rates. In conclusion, unlocking the sector's potential requires coordinated strategic interventions focused on genetic improvement, disease control, market linkages, and supportive policies.